Distress Tolerance Levels and its Relation with Clinical Parameters in Psoriasis Disease - Gurok, Mehmet Gurkan; Gurok, Nese Gocer; Demir, Betul; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2022)
Background: Psoriasis is a chronic inflammatory disorder with squamous erythematous lesions where genetic predisposition, trauma, infections, drugs, smoking and psychologic factors may play a role in its etiology. Objective: In this study we aimed to elaborate the stress tolerance levels of the patients with respect to clinical parameters. The findings of this research could drive physicians treatment attributes to enhance the importance of psychological streamline of the individual and the severity of the disease. Methods: A total of 45 psoriasis patients without any disease have been erolled in the study. The control group consisted of 45 healthy volunteers with similar baseline demographics but no physical or psychiatric disease. Both of the groups were evaluated with Psoriasis Severity Index (PASI), Socio-demographic and Clinical Data Form, Distress Tolerance Scale (DTS), Beck Depression Inventory, State and Trait Anxiety Inventory. Results: Both the patients and the control group had similar baseline demographics. Distress Tolerance Scale and its subgroup analysis showed statisticaly significant outcomes. DTS total scores (p<0.001), the DTS tolerance scores (p<0.001), the DTS scores regulation (p<0.0014), the DTS self efficacy scores (p<0.003) were statisticaly lower compared to control group. In terms of Beck Depression Inventory (p=0.001) and Anxiety Scores (both State p<0.001 and Trait p=0.002) were also at a higher rate than healthy volunteers. Conclusion: Psychological problems are common in psoriasis and may lead to the deterioration of the clinical course. In this study we have determined that stress tolerance highly varies between patients and psychotherapy might be a beneficial option for treatment success and prognosis.
Keywords: Psoriasis; Stress Tolerance; Depression; Anxiety